Deliberation or Aggression? Unpacking Toxic Disinhibition in TikTok's Political and Educational Discourse - Roul Alvaro Prasetyo; Elsa Nurhalisa; Budi Mulyono (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2026)
This study aims to analyze the forms of citizens' expressions and participation in the digital public sphere, as well as to uncover public opinion anomalies on a state official's policy post. The research subjects were netizens' comments on the "Digital Era Education Development Strategy" video on Vice President @gibran_rakabuming's TikTok account. A descriptive qualitative approach was applied through the computer-assisted qualitative data analysis (CAQDAS) method. The entire population of 1,353 comments was collected without sampling limitations (total sampling). Data collection was conducted from the time the post was uploaded on May 2, 2025, until April 21, 2026, using a web scraping technique via Apify. The data were then analyzed using NVivo software, encompassing sentiment analysis and lexical extraction (word cloud and word tree). The results reveal a paradoxical reality. Quantitatively, positive sentiments dominated with an 8:3 ratio. However, the qualitative lexical analysis was predominantly filled with harsh words, personal attacks (toxic disinhibition), and repetitive sentence templates. This paradox proves the occurrence of public space manipulation by cyber troops (buzzers) to manufacture fake public consent, while organic citizen criticisms were filled with emotional aggression. This phenomenon confirms a digital civility crisis. Therefore, it is recommended that the government stop opinion manipulation practices to build authentic public trust, educational institutions reorient digital literacy curricula towards digital citizenship ethics, and platforms strengthen algorithmic transparency to crack down on coordinated inauthentic behavior.